THE STOLEN WORDS AND WORKS - Renata Kenanga Rinda (Politeknik Negeri Jember, 2019)
Due to the widespread of stealing others’ words and works phenomenon a.k.a plagiarism in the higher education setting, there are many negative impacts of it in writing classrooms. One of the examples is that the teaching’s objective is behind from the reach. It happens because the score gathered is not collected from the students’ original works. In addition, in the future day, plagiarism also creates poor academic integrity that leads to poor work ethic. Considering its implications, this explanatory research aimed at explaining the students’ reasons for plagiarizing was conducted. Thirty higher vocational university students in writing class were involved as participants. Then, to collect the data, a set of questionnaire that composed of 16 statements was distributed. By the end, it was found that there are three major reasons that activated the students to plagiarize which were the development of technology, the students’ characteristics and behaviors, and teaching stuff and methodological aspects. By explaining the students’ reasons to plagiarize, it is hoped that its negative impact can be solved and its occurrence in the forthcoming day can be prevented. Keywords: plagiarism, reasons, writing